(S)-(−)-Fluorenylethylchloroformate (FLEC); preparation using asymmetric transfer hydrogenation and application to the analysis and resolution of amines. Issue 43 (25th October 2019) - Amin, Mohammad A.; Camerino, Michelle A.; Mountford, Simon J.; Ma, Xiao; Manallack, David T.; Chalmers, David K.; Wills, Martin; Thompson, Philip E.
Abstract: Fluorenylethylchoroformate (FLEC) is a valuable chiral derivatisation reagent that is used for the resolution of a wide variety of chiral amines. Herein, we describe an improved preparation of ( S )-(−)-FLEC using an efficient asymmetric catalytic transfer hydrogenation as the key step. We also demonstrate the application of FLEC as a chiral Fmoc equivalent for chiral resolution, with facile deprotection, of tetrahydroquinaldines, and its capacity for inducing regioselective outcomes in nitration reactions. Graphical abstract: Image 1 Highlights: Enantioselective reduction of a challenging class of ketone with recrystallization to >97% ee.  Just 45 mg of catalyst generates, after recrystallisation, 3.80g of product in >97% ee (72% yield). Synthesis of an asymmetric version of Fmoc-chloride (FLEC); both a protecting group and a chiral resolving agent. Use of FLEC to resolve cyclic amines, through formation of a carbamate derivative. FLEC is stable to synthetic transformations of attached group, but can be readily removed when required.